1
madhumitha harishankar
·2010-06-15 09:31:05
Let σ = mass density of rope
Now, momentum of rope= σL dx/dt
F=dp/dt = σL d2x/dt2 = (σx)g, as gravitational force is responsible for change in momentum.
d2x/dt2 = gx/L
On solving the differential,
x(t)= Ae^(t √(g/L) ) + Be^(-t √(g/L) )
1
madhumitha harishankar
·2010-06-15 09:37:25
Finding the velocity at the end is pretty simple.
KE at end=mv2/2 = (σL) (v2) / 2
KE gained=loss in PE
PE loss= mgh = (σL) (g) (L/2)
Equating KE and PE expressions,
v= √(Lg)
1
Sonne
·2010-06-15 10:03:59
concept: force generated due to variable mass
F_r=v_r\frac{dm}{dt} \\ m=\sigma x\\ \frac{dm}{dt}=\sigma\frac{dx}{dt}\\ F_r=\sigma v_r^2\\ F_r=\sigma (2gx)
F_{net}=\sigma g (x+X) -F_r \\ \sigma x \frac{dv}{dx}=\sigma g(X-x)
now integrate with proper limits to get
v(x)
and then write
v(x)=dxdt
and again integrate to get
x as a function of time